2020
DOI: 10.14573/altex.2001221
|View full text |Cite
|
Sign up to set email alerts
|

Automated screening for oxidative or methylation-induced DNA damage in human cells

Abstract: ods for risk assessment and classification of chemicals. When establishing new test methods, it is imperative to implement the 3R principle where possible. Ideally such tests should be animal-free and should rely on human-relevant biological systems (Beken et al., 2016;Knudsen et al., 2019).The comet assay is the gold standard in many laboratories for genotoxicity measurements. With its high sensitivity and broad scope of application, it is an attractive technique for analyzing DNA damage induction and repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Independent of the cell type tested, these studies consistently showed much a stronger increase in DNA strand break formation upon application of Fpg/Ogg1. These results are also consistent with a recent study, which demonstrated the absence of directly induced strand breaks by bromate up to a concentration of 200 µM, while Fpg-sensitive sites were detected already at 50 µM in human THP1 cells (Mack et al 2021 ). Taken together, these studies again indicate that bromate mostly induces oxidative DNA damage, which can be converted to DNA strand breaks during base excision repair.…”
Section: Modes Of Actionsupporting
confidence: 93%
See 1 more Smart Citation
“…Independent of the cell type tested, these studies consistently showed much a stronger increase in DNA strand break formation upon application of Fpg/Ogg1. These results are also consistent with a recent study, which demonstrated the absence of directly induced strand breaks by bromate up to a concentration of 200 µM, while Fpg-sensitive sites were detected already at 50 µM in human THP1 cells (Mack et al 2021 ). Taken together, these studies again indicate that bromate mostly induces oxidative DNA damage, which can be converted to DNA strand breaks during base excision repair.…”
Section: Modes Of Actionsupporting
confidence: 93%
“…In the latter study, significant removal of 8-oxo-dG lesions was observed after 21 h; however, it is not completely clear if this effect was due to repair or dilution of lesions as a consequences of cell proliferation. In a recent study, using a modified FADU assay, significant induction of Fpg-sensitive sites was observed after treatment of human THP1 macrophage-derived cells for 2 h already at concentrations ≥ 50 µM potassium bromate (Mack et al 2021 ).…”
Section: Modes Of Actionmentioning
confidence: 99%
“…HTS methods are defined as the use of automated tools to facilitate rapid execution of a large number and variety of biological assays that may include several test substances in each assay [ 162 ]. 134 publications have been found applying the keywords “genotoxicity & high throughput“ [ 163 , 164 , 165 , 166 , 167 , 168 ], although only 14 of them related to NMs ( Table 1 ).…”
Section: High Throughput Methodsmentioning
confidence: 99%
“…Here, we focus particularly on the detection of DNA strand breaks as one well-known type of DNA damage. In this context, two assays shall be highlighted: the comet (or single-cell gel electrophoresis) assay which is one of the most used assays for the detection of DNA strand breaks and the FADU (fluorimetric detection of alkaline DNA unwinding) assay as a new emerging semiautomated technology [19,20]. The comet assay was originally developed in 1984 by Ostling and Johanson and further modified in 1988 by Singh and colleagues [21,22] and is commonly used to determine the induction of DNA breakage by genotoxic agents and ionizing radiation at the level of individual cells.…”
Section: Introductionmentioning
confidence: 99%
“…The novel semi-automated version of this assay enables the fast assessment of DNA breakage in a 96-well-plate format and the integration of different control samples for ENM interference detection. Very recent research has extended its field of application to the detection of oxidative and methylation-induced DNA damage [19].…”
Section: Introductionmentioning
confidence: 99%